2021
DOI: 10.3389/fpls.2021.686024
|View full text |Cite
|
Sign up to set email alerts
|

A Small Guanosine Triphosphate Binding Protein PagRabE1b Promotes Xylem Development in Poplar

Abstract: Rab GTPases are the subfamily of the small guanosine triphosphate (GTP)-binding proteins which participated in the regulation of various biological processes. Recent studies have found that plant Rabs play some specific functions. However, the functions of Rabs in xylem development in trees remain unclear. In this study, functional identification of PagRabE1b in Populus was performed. Quantitative reverse transcription PCR (qRT-PCR) results showed that PagRabE1b was highly accumulated in stems, especially in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Several other genes have been found to promote cambial activity and xylem development in poplar, together with plant height. For instance, the overexpression of PagRabE1b encoding a small guanosine triphosphate (GTP)-binding protein leads to an increased xylem width by 27-50% and thicker xylem fiber cell walls (Liu et al, 2021). In another study, the overexpression of PagSAG101a induced increased plant height, as well as increased internode number and stem diameter, xylem width (by 5.1-14.7%), and secondary cell wall thickness while opposite phenotypes were observed for PagSAG10a knock-out plants (He et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Several other genes have been found to promote cambial activity and xylem development in poplar, together with plant height. For instance, the overexpression of PagRabE1b encoding a small guanosine triphosphate (GTP)-binding protein leads to an increased xylem width by 27-50% and thicker xylem fiber cell walls (Liu et al, 2021). In another study, the overexpression of PagSAG101a induced increased plant height, as well as increased internode number and stem diameter, xylem width (by 5.1-14.7%), and secondary cell wall thickness while opposite phenotypes were observed for PagSAG10a knock-out plants (He et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of protoplasts from stem-differentiating xylem was carried out as previously described (Lin et al, 2014;Liu et al, 2021) with minor modifications. Briefly, the stem below the 5 th internode was separated into bark and wood and then cut into about 10 cm-long segments.…”
Section: Isolation Of Stem-differentiating Xylem Protoplastsmentioning
confidence: 99%
“…To isolate protoplasts from hybrid poplar 84K, we used stems harvested from six 3-month-old 84K plantlets (Figure 2A). We then separated the bark and wood tissues of stems below the 5 th internode and obtained free protoplasts from the differentiating xylem using a previously described digestion method (Lin et al, 2014;Liu et al, 2021). Stem sectioning showed that about 10 layers of differentiating xylem cells were released by enzyme digestion (Figure 2B).…”
Section: Harvesting Protoplasts From Differentiating Xylemmentioning
confidence: 99%